2020
DOI: 10.33578/jtlee.v3i1.7826
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 7E Learning Cycle Model toward Students' Learning Outcome of Basic Science Concept

Abstract: This study aims to investigate the effect of the application of the 7E Learning Cycle Model to the learning outcomes of the Basic Science Concepts of SD 2. This research is a quasi experimental study with a Randomized pretest-posttest Control Group Design. The population of this study was all students of PGSD semester 2 STKIP ADZKIA Padang in the 2018/2019 school year. Samples were taken at random so one class was chosen as the experimental class and one class as the control class. The experimental class uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This is supported by study findings (Nur & Noviardila, 2021), which show that employing the Learning Cycle model can improve primary school students' learning outcomes and enable thematic learning objectives to be met. In accordance with this, the 7E Learning Cycle model's effect can increase student learning results for basic science ideas (Marfilinda et al, 2020). Furthermore, study (E. Wulandari et al, 2022) demonstrates that the interactive PowerPoint-assisted 5E learning cycle model has an influence on the learning outcomes of single and mixed substance scientific learning for SD Al-Madina fifth grade students in 2020/2021.…”
Section: Resultsmentioning
confidence: 59%
“…This is supported by study findings (Nur & Noviardila, 2021), which show that employing the Learning Cycle model can improve primary school students' learning outcomes and enable thematic learning objectives to be met. In accordance with this, the 7E Learning Cycle model's effect can increase student learning results for basic science ideas (Marfilinda et al, 2020). Furthermore, study (E. Wulandari et al, 2022) demonstrates that the interactive PowerPoint-assisted 5E learning cycle model has an influence on the learning outcomes of single and mixed substance scientific learning for SD Al-Madina fifth grade students in 2020/2021.…”
Section: Resultsmentioning
confidence: 59%
“…Based on the results of observations of students regarding the affective learning outcomes, the attainment assessed by the researcher in the attitudes of the aspects ranging from: 1) discipline, indicators of arriving on time that there is one student who is late, indicators of following learning that students do not play in class, indicators of discipline during learning that students obey the rules in the class, the indicator of being able to complete the task is one student who does not complete the task on time [13]. 2) cooperation, on indicators of being able to find materials for students to prepare practicum materials, on indicators of being able to find answers together with students being able to work together with their groups, on indicators of being able to carry out group discussions students can complete the task together, the indicators come to find solutions here, students are directly involved [14]. 3) responsibility, the indicators participate in completing the given task that students play a role in completing it, the indicators are able to avoid cheating students do not cheat, on the indicators of doing what has been said without being asked or taught, students are able to complete the assigned task, on indicators perform individual tasks well that learners are able to complete tasks such as homework, or other individual tasks [15].…”
Section: A Affective Aspectsmentioning
confidence: 99%
“…Several studies have been carried out on the effectiveness of constructivist teaching approaches on students' learning. The studies about the instructions based on the learning cycle model showed that learning cycle approaches help students improve academic achievement (Khan et al, 2020); self-efficacy (Puspita & Fardillah, 2021); critical thinking skills (Marfilinda et al, 2020;Tecson et al, 2021); retention (Abdullahi et al, 2021;Wodaj & Belay, 2021); science process skills (Khairani et al, 2021;Komikesari et al, 2020;Silitonga et al, 2021) and attitudes toward science (Abdullahi et al, 2021;Ören & Tezcan, 2020).…”
Section: Introductionmentioning
confidence: 99%